FAKTOR RISIKO KEJADIAN YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM TIFOID PADA ANAK DI WILAYAH KERJA PUSKESMAS SUI KAKAP DAN PUSKESMAS SUI DURIAN - Kusuma, Bagus Fendi; Saleh, Ismael; Selviana, Selviana (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Background: Typhoid fever is a life-threatening illness caused by the bacterium Salmonella Typhi. Typhoid and paratyphoid germs are passed in the faeces and urine of infected people. Children are the most vulnerable groups affected by typhoid fever. In 2014 (January-May), as many as 118 cases of typhoid fever occurred at work area of Puskesmas Sui Kakap. It was the highest rate of typhoid cases. Meanwhile, Puskesmas Sui Durian ranked the third of typhoid fever case. As many as 49 cases took place in 2014 (January-May).Aim: This study aimed to find out the correlation of typhoid fever cases in children at work area of Sui Kakap and Sui Durian public health centers.Method: A case control design was carried out in this study. The respondents were 50 children; 25 case group and 25 control group. They were selected by using simple random sampling. Then the data were statistically analyzed by using chi square test with the validity level of 95%.Result: The study revealed two findings. First, there were significant correlation of hand washing after defecation (p value= 0,024; OR=4,846), heating food habits (p value= 0,024; OR =3,77), instant food consumption (p value= 0,031; OR= 4,12), and typhoid fever in children. Second, there were no correlation of vegetables and fruits intake (p value =0,771), food presentation (p value= 0,702), and drinking water boiling method (p value=0,744).Suggestion: As a result, to avoid typhoid fever in children, parents should ask their children to wash their hands properly, direct them to pick healthy snacks, and heat the food before consumption (max. 6 hours after the initial cooking).Keywords: Typhoid, children, hand washing.